Defining suitable areas for bioclimatic comfort for landscape planning and landscape management in Hatay, Turkey - Adiguzel, Fatih; Cetin, Mehmet; Kaya, Efdal; Simsek, Mesut; Gungor, Senay; Bozdogan Sert, Elif (Springer Science and Business Media LLC, 2019)
This study is based on an area in Hatay, Turkey, and involves examining all weather and climate-related data that can be used to determine its suitability for the bioclimatic comfort. It attempts to explain bioclimatic comfort and describes in detail all the variables that make this contemporary concept and why it is important from a landscape architecture planning point of view. According to Koppen climate classification, the general climate character of the study area is classified as medium-altitude, warm summer, and climate type with mild or winters with Csa-Csb letters. As the area is very large in terms of total area, the findings were different across the whole area; which means that some parts were bioclimatic-comfort-friendly and other parts were not to varying degrees. June is the month in which suitable areas cover the province’s largest area. Because temperatures have reached a suitable level in terms of climatic comfort, humidity and wind speed have increased. In climatic map result, it shows that Hatay is the highest region area with high altitudes of regions in the center. The examination for thermal comfort took place for months. Hatay’s results show that it serves as a helper in future planning of landscape: planning that brings the comfort of bioclimatic to the level of highest and that helps determine new region settlement in Hatay. The study finally proposes that it paves the way for future researches and studies to ultimately standardize bioclimatic comfort in landscape architecture and urban planning that allows achieving the optimal planning objectives in all aspects.
Keywords: Turkey; Geographic Information Systems (GIS); Urban design and management 1; Management practice; Tilia Tomentosa | Electrometallurgy | Arcview; Geographic information systems (GIS); Land management; Urban planning; Burdur; Urban design; Urban design and management; Meteorology & Atmospheric Sciences; Urban; Hatay; Urban climate; Landscape principles; Sustainable cities; Geographic Information Systems (GIS; Bioclimatology; Bioclimatic region; Landscape structure; Planning process; Sustainability; Temperature effect; Climatic elements; Landscape principles .; 11. Sustainability; 15. Life on land; 13. Climate action